Medical device-related pressure injuries in critical patients: prevalence and associated factors - Sabrina Guterres da Silva Galetto; Eliane Regina Pereira do Nascimento; Patrícia Madalena Vieira Hermida; Josefine Busanello; Luciana Bihain Hagemann de Malfussi; Daniele Delacanal Lazzari (SciELO, 2021)
ABSTRACT Objective: To determine the prevalence of medical device-related pressure injuries in critical patients and analyze the associated factors. Method: Epidemiological, cross-sectional study. Sociodemographic, clinical and medical device data were collected. Inspection of the skin/mucous membranes was performed to identify and classify the injuries. Analysis using descriptive statistics, Poisson regression and the Spearman correlation coefficient. Results: Ninety-three patients were evaluated and 58 developed injuries, with a prevalence of 62.4%. Injuries by the orotracheal tube (50%), nasogastric tube (44.1%) and urinary catheter (28.6%) were the most prevalent, and the most affected regions were, respectively, the auricular (79.5%), nasal ala (86.7%) and urethral meatus (76.9%). Factors associated with injuries were severe edema (p = 0.005), low Braden (p<0.001) and Glasgow (p = 0.008) scores, length of stay in intensive care (p<0.001) and hospitalization diagnosis classified as other causes (p<0.001). The use of more than one device (p<0.001) and a longer time of use (p<0.001) were correlated. Conclusion: The high prevalence of injuries and the associated factors indicate the need for preventive measures and risk monitoring.